Technological features of production of copper-based composites reinforced with cast iron granules by means of casting - A. S. Kalinichenko; V. A. Sheinert; V. A. Kalinichenko; A. G. Slutsky (Литьë и металлургия)
Increasing the operational reliability of friction units is one of the priorities for mechanical engineering, which requires the creation of effective tribotechnical materials. First of all, this applies to sliding bearings, which are used in various friction units in a wide range of operating conditions and must meet a number of requirements: low coefficient of friction, high wear resistance and fatigue resistance, as well as good thermal conductivity, workability, corrosion resistance and machinability, low coefficient of linear expansion and low cost. It is problematic to satisfy these requirements in real conditions; therefore, different friction materials that are best suited to specific conditions have been developed. In particular, cast composite materials (LCM) have been developed, which have found application in various friction units operating in severe operating conditions. Currently, the theoretical foundations of the mechanics of reinforced composite materials are well developed, and a significant progress has been achieved in their material science. However, there are still many problems associated with the choice of optimal technology ensuring the achievement in practice of the predicted composites properties by theory, control of interfacial interaction to improve the stability of the structure and properties of CM, with the development of new types of reinforcing elements that can raise the level of composite performance.In the present work results of scientific and experimental studies on the development of casting technology (solid-liquid synthesis) for obtaining composite materials with macroheterogeneous structure have been summarized. The structures of composites are studied for different methods of synthesis, as well as for different chemical composition of cast iron granules. The prospects of using white vanadium cast iron granules as a reinforcing phase are shown.